Problematika Korupsi Dana Desa Pada Pelaporan Dan Pertanggungjawaban Keuangan Desa Berdasarkan Prinsip Transparansi, Akuntabilitas, Dan Partisipatif - Adi Fauzanto (Widya Yuridika, 2020)
The development of the community and the post-reform state implemented a decentralized system. Impacts on the formation of regional and structural governance including Village. The village itself is an element of the smallest scope of the region, an important element in all fields of development in the country of Indonesia. The form of village development is the allocation of funds which is one of the village's financial revenues, commonly referred to as the Village Fund. The realization of the objectives of village funds is not achieved easily, there are problems with the management of village funds, namely corruption of village funds. The reconstruction of the village financial accountability and reporting system is needed, both from the beginning of the planning process to the disbursement of the Village Fund using the principles of transparency, accountability, and participation to produce an analysis of the problem. Village Fund Corruption due to the increase in village funds provided by the central government to local governments, and the inadequate management system of the authorized officials. The cause comes from the low quality of the human resources of the village apparatus supported by the lack of transparency, accountability, and participation from the community. In this case, HR (human resources) is needed in managing the organization so that the financial statements can be carried out properly, also it requires community involvement in the management and accountability of the Village Fund.